Muscle activation patterns in football code athletes with chronic groin pain: a case control study. Issue 2 (20th January 2011) - Graham, Jennifer; Morrissey, Dylan; Small, Claire; Twycross-Lewis, Richard; Woledge, Roger
Abstract : Background: Groin pain is a common injury among football code athletes. The repetitive turning, twisting and kicking involved in such sports place supra-physiological stresses through the pelvic region. It has been suggested that rehabilitation of chronic groin pain requires specific sequencing of muscle activation to be effective. This has been identified as being a difference in subjects with groin and sacroiliac joint pain during lower limb movement. Aims: The aims of this paper were to; (1) identify any differences in muscle activation before and during an active straight leg raise between football code groin sufferers and controls and to (2) highlight any differences in muscle activity between the symptomatic and asymptomatic sides in the groin sufferers before and during an active straight leg raise. Methodology: Nine subjects with groin pain and nine matched controls (matched according to age, weight and height) were used. Surface electromyogenic (EMG) electrodes were placed on six bilateral muscle groups – rectus femoris, biceps femoris, adductor longus, internal oblique, multifidus and gluteus medius. Movement was qualified with an active motion tracking system, while the subject lay on two force plates and performed an active straight leg raise manoeuvre. EMG, force and pelvic motion was analysed to demonstrate any muscle activation differences between the symptomatic and asymptomatic group. Results: A significant difference was found between the symptomatic and asymptomatic limbs in both ipsilateral and contralateral adductor longus muscles (p<0.03, p<0.01), both ipsilateral and contralateral gluteus medius muscles (p<0.02, p<0.04) and ipsilateral rectus femoris (p<0.02) at initial onset of movement. During the movement, a significant difference was found between the control and case groups (both symptomatic and asymptomatic side) in the ipsiateral and contralateral internal oblique muscles (p<0.05, p<0.04) and the ipsilateral adductor longus (p<0.01). Conclusion: This study has shown that there are differences in the muscle groups supporting the pelvis during lower limb movement. Of this study's findings, the most notable was that the gluteus medius and adductor longus muscles showed decreased activity in the groin sufferers group. The Adductor Longus decrease correlates with current literature, however the decreased activation of gluteus medius suggests that this muscle group should be integrated into the groin rehabilitation.